1997
DOI: 10.1002/(sici)1098-2280(1997)30:4<385::aid-em3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Nature of mutation in the humanhprt gene following in vivo exposure to ionizing radiation of cesium-137

Abstract: The current study comprises the analysis of mutations in 10 individuals accidentally exposed to cesium‐137 during the 1987 radiological accident in Goiânia, Brazil. Their exposures were among the highest experienced, ranging from 1 to 7 Gy. Peripheral T‐lymphocyte samples were obtained 3.3 years after the original exposure and mutation was studied at the hprt locus using the 6‐thioguanine‐resistance selection assay. The mutational spectrum for the exposed population is comprised of 90 independent mutants. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…In addition, the HPRT gene is an excellent biomarker of effect because mutations at the HPRT locus have no direct clinical consequences and have been shown to reflect genome-wide mutational events (13,14). This approach for somatic mutation analysis in humans has been widely used to determine in vivo background as well as acquired somatic cell Mfs in pediatric and adult populations exposed to known and unknown environmental mutagens (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HPRT gene is an excellent biomarker of effect because mutations at the HPRT locus have no direct clinical consequences and have been shown to reflect genome-wide mutational events (13,14). This approach for somatic mutation analysis in humans has been widely used to determine in vivo background as well as acquired somatic cell Mfs in pediatric and adult populations exposed to known and unknown environmental mutagens (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular exposure to ionizing radiation induces a genotoxicity stress in cells that could result in damage of their genetic material. A 3-year follow-up study of the population accidentally exposed to high doses of ionizing radiation found 40% of missense mutations involving A:T pairs (da Cruz and Glickman, 1997;. Recently, our group surveyed the genetic variation of 12 microsatellite loci in 10 families of exposed individuals and their offspring and the mutation rate was found to be higher in the exposed families compared to the control group (da Cruz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The models using the endogenous X-linked hypoxanthine guanine phosphoribosyl transferase (hprt) gene of rodent lymphocytes as a target [Jones et al, 1985;Aidoo et al, 1997] theoretically can detect a wider range of mutations. In practice, most 6-thioguanine (6-TG)-resistant lymphocyte clones characterized at the molecular level contain only intragenic alterations in the hprt gene [Skopek et al, 1992;Mittelstaedt et al, 1995;Heflich et al, 1996;da Cruz and Glickman, 1997]. It is believed that there is a gene flanking the hprt gene that is necessary for cell survival, so that large deletions affecting this important gene cannot be recovered as hprt mutants.…”
Section: Introductionmentioning
confidence: 99%